2018
DOI: 10.1259/bjr.20170729
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage can be thicker in advanced osteoarthritic knees: a tridimensional quantitative analysis of cartilage thickness at posterior aspect of femoral condyles

Abstract: Cartilage at the posterior aspect of the medial condyle, but not the lateral condyle, is statistically significantly thicker in advanced medial femorotibial OA knees compared to non-OA knees. The thickest cartilage was located in the half most medial aspect of the posterior medial condyle. These results will serve as the basis for future research to determine the histobiological processes involved in this thicker cartilage. Advances in knowledge: This study, through a quantitative tridimensional approach, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
4
13
1
Order By: Relevance
“…In contrast to the study hypotheses, no increase in cartilage thickness was found in either the load-bearing VOIs of the medial compartment in early OA nor in the non-load-bearing VOIs of the medial and lateral compartments between OA radiographic severities. This differs from previous evidence of cartilage thickening in the medial load-bearing VOIs in the early stages of OA and in areas of lesser loading throughout the disease [ 11 , 12 , 13 , 14 , 28 , 31 , 32 ]. The causes for medial cartilage thickness increases observed in the early stages of the disease in the general medial knee OA population are not entirely understood [ 13 , 29 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the study hypotheses, no increase in cartilage thickness was found in either the load-bearing VOIs of the medial compartment in early OA nor in the non-load-bearing VOIs of the medial and lateral compartments between OA radiographic severities. This differs from previous evidence of cartilage thickening in the medial load-bearing VOIs in the early stages of OA and in areas of lesser loading throughout the disease [ 11 , 12 , 13 , 14 , 28 , 31 , 32 ]. The causes for medial cartilage thickness increases observed in the early stages of the disease in the general medial knee OA population are not entirely understood [ 13 , 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In a healthy knee joint, anabolic and catabolic processes of cartilage are balanced to maintain tissue metabolic homeostasis [ 30 ]. Using evidence from animal models, it is suggested that early cartilage thickening may be due to a reparative, anabolic response to the initial cartilage damage, resulting in increased proteoglycan production and apparent cartilage hypertrophy [ 24 , 31 , 32 ]. In the later stages of the disease, the same anabolic signaling may exist, but its effect is likely only visible in areas of cartilage not exposed to load-induced degradation, such as the most posterior aspect of the medial condyle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…34 Although no clinical association can be drawn between our findings and future degenerative changes, it is interesting to acknowledge the articular cartilage on the posterior aspect of the medial condyle was found to be the most affected area in advanced osteoarthritic knees. 35 Our findings are also consistent with a previous study by Goyal et al, 36 who showed that on the tibial surface, the medial, or posteromedial half of the medial tibial plateau, are the most common areas to suffer chondral damage.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the regression analysis of men and women, we found that the cartilage thickness in the FMP region of bilateral knees of women increased with age. Previous studies ( 28 , 29 ) also reported that the cartilage thickness in the FMP area could increase in OA knees compared with non-OA knees without considering the sex differences. Therefore, we infer that the thickening of cartilage in the FMP area is a physiological change related to hormones.…”
Section: Discussionmentioning
confidence: 90%